A Historical and Philosophical Perspective of Social Support Systems - Duuki, Richard; Edaku, Charles; Ongodia, Simon Peter (East African Journal of Arts and Social Sciences, 2025)
This manuscript offers a comprehensive analysis of the philosophical and historical dimensions of social support systems, aiming to establish a foundational body of knowledge to guide future research in this domain. By examining various philosophical traditions, the study delves into the evolution of social support concepts, encompassing Greek social philosophy, Roman social philosophy, early Christian thought, and the philosophy of Ubuntu. The manuscript elucidates how these diverse perspectives have shaped contemporary understandings of social support, highlighting both the continuities and transformations over time. Through this historical and philosophical exploration, the paper seeks to provide a robust framework for analyzing and enhancing modern social support systems, ultimately contributing to more informed and effective support structures in contemporary society